ONLINE NUCLEAR ORIENTATION OF SB-116M,G, IN-116 AND SB-114 - Booth, M; Rikovska, J; Stone, N; Zimmerman, B; Walters, W; Mantica, P; Carter, H; Kern, B (Kluwer Academic Publishers, 1993)
Angular distribution data for gamma radiation from separated116,116m,114Sb and116In oriented on-line at mK temperatures at the UNISOR Nuclear Orientation Facility, Oak Ridge, is reported. Mixing ratios of three 2+ states in116Sn are deduced. The magnetic moments of116mSb, (+)2.59(22) μN and114Sb, (+)1.72(8) μN, are extracted with full allowance for incomplete spin-lattice relaxation. Single particle descriptions of these states are briefly discussed. © 1993 J.C. Baltzer AG, Science Publishers.